Analysis of the agricultural position of Jászfényszaru's economy - Illés, Gergő; Némedi-Kollár, Kitti (Studia Mundi – Economica, 2017)
Jászfényszaru has one of the most important today’s resources, it has industry. However, the utilization of agricultural land has a long history in the settlement, but nowadays the industry basically determines the life of the small town. The significant industrial concentration resulting labor shortages, which also affects the agricultural employment. The number of agricultural companies is showing a declining trend, but the production of social employment has appeared as a new element in the system.